Bycatch risk assessment and spatial restrictions of fishing: a study focusing on a critically endangered elasmobranch in central Mediterranean waters - Irida Maina; Archontia Chatzispyrou; Nikolaos Fotiadis; Stefanos Kavadas; Amaia Astarloa; François Bastardie; Evgenia Lefkaditou; Vassiliki Vassilopoulou (Estuarine, Coastal and Shelf Science, 2026)

tools4MCDA: An R-Package to estimate spatial fishing effort, weight and value of landings using multi-criteria decision analysis - Irida Maina; Dimitris Politikos; Stefanos Kavadas (Ecological Modelling, 2026)

Assessment of Bottom Trawl Impacts on the Status of Seabed Communities in European Seas - Jan Geert Hiddink; Sebastian Valanko; Luke Batts; Esther D. Beukhof; Mats Blomqvist; Stefan Bolam; Belén Calero; Michele Casini; Marina Delgado; Jochen Depestele; Joanna Desmidt; Gabriele Di Bona; et al. (Fish and Fisheries, 2026)
Bottom trawling affects seabed habitats, but its large‐scale impacts remain poorly quantified. Assessment of trawling impacts is essential to support monitoring and achieving sustainability objectives under international conventions, sustainable development goals, and seafood certification programs. We present a Europe‐wide quantitative assessment of bottom trawling impacts, accounting for regional seabed‐community sensitivity drivers, across the Baltic, Atlantic, Mediterranean and Black Sea continental shelves. Using two risk‐based indicators of seabed status—Relative Benthic Status determined as benthic community biomass relative to seabed fauna carrying capacity (RBS tot ) and RBS sen (biomass of the 10% most sensitive fauna relative to carrying capacity)—we found substantial regional and habitat differences. The Black, Baltic and Aegean‐Levantine Seas showed low trawling intensity and high seabed status across habitats. In contrast, the Western Mediterranean, Ionian and Central Mediterranean and Adriatic Seas were the most severely impacted. Trawling affected the sensitive species biomass fraction more strongly than the total community biomass. RBS tot was in good condition (here chosen as RBS > 75% for epifauna) for over 79% of habitat‐ecoregion combinations. In contrast, RBS sen met this threshold in only 46% of these. A strong correlation emerged between the mean trawling intensity and RBS tot and RBS sen , allowing the use of SAR to estimate ecosystem status. This relationship can support decisions on where, and by how much, SAR reductions are needed to achieve good environmental status in regions where no detailed assessment is available. Our approach provides a quantitative framework to balance fishery production with ecosystem sustainability, offering tools for environmental and fisheries management in Europe.

Integrating benthic ecological status and spatial planning to guide sustainable bottom-contacting fisheries in the Eastern Mediterranean - Irini Tsikopoulou; Irida Maina; Nadia Papadopoulou; François Bastardie; Chris J. Smith (Frontiers in Marine Science, 2026)
To inform ecosystem-based fisheries management in line with the EU legislation objectives for marine fisheries, we evaluated the ecological outcomes of alternative spatial management scenarios to fisheries that consider the ecological impact of bottom trawling on the benthic ecosystem in the Eastern Ionian Sea. Trawling intensity in terms of swept area ratio (SAR) and benthic community sensitivity were combined to estimate the relative benthic status (RBS). Then, five management scenarios were tested. The scenarios include four static closure scenarios (below 800 m, below 600 m, the least-trawled 10% of fishing grounds, and areas shallower than 150 m), where trawling is completely excluded without fishing effort redistribution, and one with a trawl ban in all marine protected areas, where fishing effort displacement is modelled dynamically. Baseline RBS was high (>0.9 on a scale of 0 to 1 where 1 is unaffected benthic community) in all habitats, reflecting relatively low benthic degradation due to bottom trawling. Excluding bottom trawling from areas shallower than 150 m in depth produced the greatest improvements, while thresholds at 600 or 800 m depth, and the closure of the 10% least-trawled grounds, had no significant effects on benthic ecological status. Closure of trawling in the marine protected areas produced mixed outcomes, with improvements in some habitats but localized declines due to displaced effort in others. Our study demonstrates the value of including benthic indicators in spatial management strategies to guide adaptive, evidence-based fisheries governance, balancing conservation objectives with socio-economic sustainability.

Anticipating how spatial fishing restrictions in EU waters perform to protect marine species, habitats, and dependent fisheries - François Bastardie; Amaia Astarloa; Logan Binch; Isabella Bitetto; Dimitrios Damalas; Jochen Depestele; Pierre-Yves Hernvann; Sigrid Lehuta; Jonas Letschert; Irida Maina; Stéphanie Mahévas; Georgia Papantoniou; et al. (Frontiers in Marine Science, 2025)
This study investigates the implications of spatial management strategies on fish populations and fisheries across EU waters, particularly focusing on establishing potential areas for fishing closures to protect nurseries, benthic communities, and biodiversity hotspots in the Northeast Atlantic and Mediterranean Sea. The research addresses the effectiveness of prohibiting certain fishing practices in the context of the EU Common Fisheries Policy (CFP). We investigate spatial- and effort-based fisheries management strategies based on spatial ecosystem modelling, which provides insights into species interactions and distribution shifts, and bioeconomic fisheries models which incorporate finely defined fishing fleets and economic dynamics. Our findings emphasize that redistributing fishing effort without reducing overall effort and catches may negate intended decreases in mortality rates of sensitive marine species or restoration of vulnerable marine habitats to the status targeted by the European marine legislation (EU Marine Strategy Framework Directive MSFD). We highlight the complex interplay of social, economic, ecological, and institutional factors influencing fishers’ decision-making in effort displacement. As the proportion of closed regions increases, potential effects on marine ecosystems can even be damaging in the short term to some sensitive species (such as the endangered, threatened and protected species ETP) and vulnerable habitats (with currently high relative benthic status RBS). This emphasizes the importance of the placement of closed areas and of combining area-based management with other fishery management measures. Findings from case studies in the North Sea, Mediterranean Sea, and Bay of Biscay indicate that prohibiting certain fishing practices in designated areas will likely induce short-term economic losses on specific fishing fleets. Where the prohibitions contribute to improved selectivity or productivity of the fish stocks, these losses may be regained in the long term. Finally, the long-term benefits for marine life that are expected through the spatial protection of vulnerable life stages and habitats will rely on the extent to which climate change affects ocean productivity and distribution of species and habitats.

Modeling the spatial distribution and abundance of deep‐water red shrimps in the Mediterranean Sea: a machine learning approach - Elena Catucci; Diego Panzeri; Simone Libralato; Gianpiero Cossarini; Germana Garofalo; Irida Maina; Stefanos Kavadas; Federico Quattrocchi; Giulia Cipriano; Roberto Carlucci; Sergio Vitale; Chryssi Mytilineou; et al. (Fisheries Research, 2025)

A geoportal of data and tools for supporting Maritime Spatial Planning in the Adriatic-Ionian Region - Stefano Menegon; Amedeo Fadini; Luisa Perini; Alessandro Sarretta; Daniel Depellegrin; Elisabeth De Maio; Giulio Farella; Marica Landini; Carlo Fava; Christian Ferrarin; Michol Ghezzo; Elisabetta Manea; et al. (Environmental Modelling & Software, 2023)

The MINOUWApp: a web-based tool in support of by-catch and discards management - Lorenzo D’Andrea; Aida Campos; Karim Erzini; Paulo Fonseca; Simone Franceschini; Stefanos Kavadas; Irida Maina; Francesc Maynou; Tommaso Russo (Environmental Monitoring and Assessment, 2020)
Current fishing practices often do not allow adequate selection of species or sizes of fish, resulting in unwanted catches, subsequently discarded, with the consequent negative effects on both marine communities and fisheries profitability. The cross-analysis of density patches of potential unwanted catches and distribution of fishing effort can support the identification of spatial-temporal hot-spots in which the fishing pressure should be reduced to limit the amount of discards. The MinouwApp represents a technological and methodological framework to bring different, and structurally complex, sources of georeferenced data together into a simple visual interface aiming to interactively explore temporal ranges and areas of interest. The objective is to improve the understanding of fisheries dynamics, including discards, thus contributing to the implementation of discard management plans in a context of participative, ecosystem-based fisheries management strategies.

Small-Scale Coastal Fishing Shapes the Structure of Shallow Rocky Reef Fish in the Aegean Sea - Maria Sini; Konstantinos Vatikiotis; Zoi Thanopoulou; Christos Katsoupis; Irida Maina; Stefanos Kavadas; Paraskevi K. Karachle; Stelios Katsanevakis (Frontiers in Marine Science, 2019)

Cumulative impacts from multiple human activities on seagrass meadows in eastern Mediterranean waters: the case of Saronikos Gulf (Aegean Sea, Greece) - Maren Myrto Brodersen; Maria Pantazi; Athina Kokkali; Panayotis Panayotidis; Vasilis Gerakaris; Irida Maina; Stefanos Kavadas; Helen Kaberi; Vassiliki Vassilopoulou (Environmental Science and Pollution Research, 2018)